Penetapan Kadar Flavonoid dan Uji Aktivitas Antioksidan Ekstrak Etanol 70%, Fraksi N-Heksana, Etil Asetat, dan Air dari Kubis Putih dan Kubis Ungu Menggunakan Metode Frap - Budi Santoso; Danang Raharjo; Desy Ayu Irma Permatasari (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Cabbage contains various vitamins such as vitamin A, vitamin C and phytonutrient compounds that are natural antioxidants. Flavonoids are compounds with antioxidant activity that can protect the body from free radicals. This study aims to determine the flavonoid content and antioxidant activity of 70% ethanol extract, n-hexane fraction, ethyl acetate, and water from white cabbage (Brassica oleracea l.) and purple cabbage (Brassica oleracea l. Var. Capitata f. Rubra) FRAP method. This study was conducted experimentally including sample preparation, phytochemical screening, simplisia characterization, determination of total flavonoid content using colorimetric method with AlCl3 reagent and quercetin was used as a comparison. Antioxidant activity testing was carried out using the FRAP method with vitamin C as a comparison measured using a UV-Visible spectrophotometer. The results showed that the total flavonoid levels contained in white cabbage and purple cabbage were 5.664 mg QE/g sample and 10.145 mg QE/sample. Ethanol extracts of white cabbage and purple cabbage n-hexane, ethyl acetate and water fractions have antioxidant capacity of 71.534 mg AAE/ gram extract, 69.651 mg AAE/ gram extract, 93.781 mg AAE/ gram extract, 74.941 mg AAE/ gram extract and 78.08 mg AAE/ gram extract, 77.913 mg AAE/ gram extract, 99.145 mg AAE/ gram extract, 76.319 mg AAE/ gram extract. It can be concluded that the antioxidant activity of purple cabbage is higher than that of white cabbage.